Antioxidant effect of Nigella sativa L. extracts on physicochemical properties of deep fried oil - Solati, Zeinab (2011)
The main objective of this study was to investigate the effect of Nigella sativa L. extract as a natural antioxidant on the physicochemical changes of frying oil. Two different techniques namely, supercritical CO2 extraction (SC-CO2) and solvent extraction were utilized to extract the oil from Nigella sativa L.seeds. These two techniques were also compared in terms of extraction yield, thymoquinone content and antioxidant activity of the extracted oil. Initially, influence of SC-CO2 variables namely, pressure, temperature and dynamic extraction time on the extraction efficiency of Nigella sativa L. oil was studied by using full factorial design. The main goal was to determine the most suitable SC-CO2 condition in order to obtain antioxidant rich Nigella sativa L. oil. The response variables studied were yield, antioxidant activity (DPPH method) and thymoquinone (TQ) quantity of the extracts. The results indicated that the highest extraction yield was obtained at 350 bar, 60 °C and 120 min, the highest antioxidant activity was achieved at 350 bar, 50 °C and 60 min and the highest thymoquinone quantity was obtained at 150 bar, 40 °C and 120 min for extraction pressure, temperature and dynamic extraction time respectively. As shown in the results from gas chromatography analysis, the major fatty acid composition of Nigella sativa L. seed oil were: linoleic acid (C18:2), oleic acid (C18:1) and palmitic acid (C16:0). The results indicated that there was no significant (p > 0.05) difference in the fatty acid composition of oil extracted by SC-CO2 and solvent extraction. The SC-CO2 extract showed higher thymoquinone concentration (4.09 mg/ml) than the extract from solvent extraction (1.06 mg/ml). The higher extraction yield was obtained by soxhlet (33.00 %) than by SCCO2 (23.20 %). Radical scavenging activity (DPPH method) of the extracts obtained by SCCO2 and solvent showed the IC50 of 2.59 and 8.26 (mg/ml) respectively. Effect of Nigella Sativa L. oil extracted by using SC-CO2 (with the highest antioxidant activity) on the frying performance of two different frying oils namely, sunflower and RBD palm olein was investigated by adding different concentration levels of 12000 and 10000 ppm of Nigella Sativa L. oil to sunflower and RBD palm olein respectively. It should be noted that two samples containing 0 ppm Nigella sativa L. oil (Control) and 200 ppm BHT were prepared to check the performance of Nigella Sativa L. oil compared to a commonly used antioxidant (i.e. BHT). The physicochemical properties (i.e. Fatty Acid Composition (FAC), Free Fatty Acids (FFA), Peroxide Value (PV), Anisidine Value (AV), Totox Value (TV), Iodine Value (IV), Total Polar Content (TPC), ultra violet absorbance at 232 and 268 nm, C18:2/C16:0 ratio, viscosity and color) of frying oils were determined during five consecutive days of frying. Results have shown that the addition of Nigella sativa L. oil to both frying oils improved their oxidative stability during the frying process. Moreover, the control sample showed the highest degree of deterioration as compared to those containing BHT and NO (Nigella sativa L. Oil). In addition, both frying oils containing 10,000 and 12,000 ppm of Nigella sativa L. extract for palm olein and sunflower oil respectively were able to stabilize the frying oil during the frying process when compared to control. From the results it could be indicated that the stabilizing effect of antioxidans were in the order of BHT > NO. These results were concluded according to the PV, TPC, C18:2/C16:0 ratio, absorbance at 232 and 268 nm and viscosity which were the best indicators of oil deterioration extent. RBD palm olein was found to be more stable than sunflower oil based on the ratio of linoleic acid (C18:2) to palmitic acid (C16:0) and fatty acid composition